2000
DOI: 10.1042/cs19990319
|View full text |Cite
|
Sign up to set email alerts
|

Internal carotid artery haemodynamics in women with polycystic ovaries

Abstract: Although polycystic ovarian syndrome (PCOS) is associated with risk factors for cerebrovascular disease, the available evidence does not demonstrate increased stroke mortality, and it has been suggested that some protective mechanisms must be operating in these women. Haemodynamic changes have been demonstrated in the pelvic vessels and aorta in this syndrome, but there have been no studies of the cerebral circulation. Since insulin resistance is a central feature of PCOS, it is of interest that cerebral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Measurements of the VA and ICA at the right and left sides have been reported in healthy adults and in various diseases. [7][8][9][10][11]25,26 In healthy individuals, the left VA was shown to be the dominant side, contrary to the right VA, which is compatible with our control group findings. Jeng and Yip, 27 who studied 447 subjects, found significant asymmetries in diameter, flow velocities, and blood flow with left-sided dominance; Seidel et al 24 showed nonsignificant left side dominance for VAs in 50 patients with nonvascular neurologic conditions; and Hong et al 28 found left VA dominance in their report about the reference values for the blood flow of the VA using color Doppler sonography in the 35 healthy Korean adults.…”
Section: Discussionsupporting
confidence: 91%
“…Measurements of the VA and ICA at the right and left sides have been reported in healthy adults and in various diseases. [7][8][9][10][11]25,26 In healthy individuals, the left VA was shown to be the dominant side, contrary to the right VA, which is compatible with our control group findings. Jeng and Yip, 27 who studied 447 subjects, found significant asymmetries in diameter, flow velocities, and blood flow with left-sided dominance; Seidel et al 24 showed nonsignificant left side dominance for VAs in 50 patients with nonvascular neurologic conditions; and Hong et al 28 found left VA dominance in their report about the reference values for the blood flow of the VA using color Doppler sonography in the 35 healthy Korean adults.…”
Section: Discussionsupporting
confidence: 91%
“…In women with PCOS significant pharmacological reactivity changes develop as well as mechanical damages of the large blood vessels [3], [4]. The changes in smooth muscle and endothelium related relaxation, as well as vasoconstriction, were studied in PCOS and in hyperandrogenic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, haemodynamic changes of internal carotid artery [4] and early predictors of endothelium dysfunction in women with PCOS were detected, as FMD (flow mediated dilatation) and nitrate-mediated dilation were significantly lower in women with PCOS than in the control group [5]. Moreover, a recent meta-analysis found a two-fold risk of coronary heart disease and stroke for patients with PCOS compared to women without PCOS [6].…”
Section: Introductionmentioning
confidence: 99%
“…did not find any significant changes in blood flow rates, PI and back pressure of the middle cerebral artery (MCA) and internal carotid artery (ICA) in PCOS; however, Lakhani et al . have shown reduced PI and back pressure in the ICA of patients with PCOS . To our knowledge, there is no study analyzing OBF parameters in PCOS patients in the current PubMed‐based literature.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Estimated mechanisms for this increased risk are cholesterol metabolism imbalance, insulin resistance and androgen excess. 14 15,16 To our knowledge, there is no study analyzing OBF parameters in PCOS patients in the current PubMedbased literature. The eye receives its blood supply from the OA by way of the CRA, short and long posterior ciliary arteries and the anterior ciliary arteries.…”
Section: Discussionmentioning
confidence: 99%